Defending Christ: the Latin apologists before Augustine - Thomas, Nicholas L. (Brepols, 2011)
This work is a discussion of the African Latin apologists prior to St. Augustine. The time-frame ranges from the end of the second century into the opening of the fourth; one of the most important locations in the formative history of Christian doctrine and practice. In turn, the literary medium of the apology carries particular significance in this period. The apologetic writings of Minucius Felix, Tertullian, Cyprian, Arnobius of Sicca and Lactantius are considered in chronological order, highlighting aspects of a collective tradition as well as more individual apologetic concerns. Common themes, shared arguments, and probable lines of influence all support a highly workable generic connection of African Latin apologetics, provided that the nuances of each text are taken into account. The purpose of this study is to contribute to the dialogue of a tradition of African Latin apologetics before Augustine of Hippo’s landmark De ciuitate dei.
paid
Keywords: 30-600; Africa; Apologetics; Apologetics Africa History Early church; ca. 30-600; Apologetics Early church; Apologetics History Early church; ca. 30-600; Apologetik; Apologétique Afrique Histoire ca 30-600 (Église primitive); Apologétique Histoire ca 30-600 (Église primitive); Arnobius; of Sicca; Catholic Church; Catholic Church Africa Apologetic works History and criticism; Catholic Church Apologetic works History and criticism; Christian literature; Early Latin authors History and criticism; Criticism; interpretation; etc; Cyprian; Saint; Bishop of Carthage; Geschichte 200-400; History; Katholische Kirche; Lateinische Kirchenväter; Minucius Felix; Marcus; Nordafrika; Tertullian; approximately 160-approximately 230; Église catholique Ouvrages apologétiques Histoire et critique